Analisis Dampak Indonesia Japan Economic Partnership Agreement terhadap Price-Cost Margins Industri Manufaktur Indonesia - Budiarti, Fitri Tri; Hastiadi, Fithra Faisal (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
Indonesia Japan Economic Partnership Agreement (IJEPA) is the first bilateral economic agreement for Indonesia. IJEPA is expected to increase Indonesia manufacture industry competition because the establishment of USDFS and MIDEC. Post IJEPA, Price-cost margins (PCM) fluctuated. PCM has been generally used as a competition indicator, because PCM related to average profit of an industry. This study uses panel data of large and small industry within 2004-2012 periods. This study conclude that IJEPA able to make PCM of manufacture industry fall through efficiency of input factors use, the cost of materials price downfall, and economies of scale in certain industries.